2017
DOI: 10.3846/bme.2017.366
|View full text |Cite
|
Sign up to set email alerts
|

Practical Application of Exclusive and Inclusive Talent Management Strategy in Companies

Abstract: The article deals with the practical application of exclusive and inclusive talent management strategies in order to form and maintain a competitive human resource potential of the company. The features of both exclusive and inclusive talent management strategies were defined and their practical appication in companies of various Lithuaniam industries was studied. The input from the respondents suggests that major companies prefer the inclusive talent management strategy, rather than exclusive. Summing up all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
1
10
0
3
Order By: Relevance
“…Due to their emphasis on talents for key positions, we can discern STM and GTM as exclusive approaches. Conversely, FITM (an inclusive approach) is a new perspective that differs from STM or GTM (Swailes, Downs, and Orr 2014;Savanevičienė and Vilčiauskaitė 2017). FITM is defined as 'the recognition and acceptance that all employees have talent, together with the ongoing evaluation and deployment of employees in positions that give the best fit and opportunity (via participation) for employees to use those talents' (Swailes, Downs, and Orr 2014, 533).…”
Section: The Definition Of Tmmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their emphasis on talents for key positions, we can discern STM and GTM as exclusive approaches. Conversely, FITM (an inclusive approach) is a new perspective that differs from STM or GTM (Swailes, Downs, and Orr 2014;Savanevičienė and Vilčiauskaitė 2017). FITM is defined as 'the recognition and acceptance that all employees have talent, together with the ongoing evaluation and deployment of employees in positions that give the best fit and opportunity (via participation) for employees to use those talents' (Swailes, Downs, and Orr 2014, 533).…”
Section: The Definition Of Tmmentioning
confidence: 99%
“…On the other hand, contenders to this exclusive approach have constructed what we call fully inclusive talent management (FITM), an approach that treats all employees as talented (Swailes, Downs, and Orr 2014;Savanevičienė and Vilčiauskaitė 2017). Facing these two contradictory approaches, Thunnissen, Boselie, and Fruytier (2013) argue that the concept of TM is too broad, while the majority of TM research wrongly deals with only organizational level variables.…”
Section: Introductionmentioning
confidence: 99%
“…The present study found that talent management is on its rise and most of the organisations across sectors are aware of or pay attention to talent development and know its importance. It is further connected to current context of lack of skilled and talented workers in the job market, as mentioned also by Savaneviciene and Vilciauskaite (2017).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, Van Zyl et al 2017add that talent management is extremely important for private sector. In the context of current lack of skilled and talented workers in the job market noticeable preference of inclusive rather than exclusive talent management can be observed (Savaneviciene and Vilciauskaite, 2017). This can lead to a conclusion that the job position obtainedmanagerial or non-managerialdoes not play significant role or any role in placement of employee in talent programme.…”
Section: Employer Branding and Criteria Of Its Applicationmentioning
confidence: 99%
“…Nevertheless, 78 further definienda were also identified that expressed the subject of TM, for example: "A player" e.g., [18], "high flyer" [23], or "star employee" [24]. As 70 out of these 78 belonged to the two approaches of the exclusive subject talent approach in line with the well-known framework of talent approaches by Gallardo-Gallardo et al [8], the dominance of the exclusive subject talent approach was noticeable in these definienda.…”
Section: Resultsmentioning
confidence: 99%